2018
DOI: 10.1002/poc.3834
|View full text |Cite
|
Sign up to set email alerts
|

5‐Phenyl‐1,3,4‐oxadiazole‐2‐thiol/polyamide‐montmorillonite microbicides nanocomposites as drug delivery system

Abstract: The preparation and structural characterization of polymeric microbicides consisting of 5-phenyl-1,3,4-oxadiazole-2-thiol covalently bound to polyamide based on diethyl-2,3-dihydroxysuccinate and polyoxypropylenetriamine Jeffamine (T 403 ) are described. Two different mole ratios of 5-phenyl-1,3,4oxadiazole-2-thiol was reacted with chloroacetylated diethyl-2,3dihydroxysuccinate followed by polycondensation with Jeffamine (T 403 ). The nanocomposites were prepared by modification of microbicide polyamides to yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…MMT plays an important role in the delivery of drugs due to its unique characteristics such as swelling and adsorption. Salahuddin et al has recently reported 5-phenyl-1,3,4-oxadiazole-2-thiol/polyamide-MMT microbicide nanocomposites in the field of drug delivery [77]. These MMTs with anionic polymers like alginate form a unique polymer silicate material that provides a superior capability of incorporating drug molecules within the structure.…”
Section: Othersmentioning
confidence: 99%
“…MMT plays an important role in the delivery of drugs due to its unique characteristics such as swelling and adsorption. Salahuddin et al has recently reported 5-phenyl-1,3,4-oxadiazole-2-thiol/polyamide-MMT microbicide nanocomposites in the field of drug delivery [77]. These MMTs with anionic polymers like alginate form a unique polymer silicate material that provides a superior capability of incorporating drug molecules within the structure.…”
Section: Othersmentioning
confidence: 99%
“…1,3,4-Oxadiazoles are known to be associated with a broad spectrum of biological activities (Salahuddin, Elbarbary, Allam, & Hashim, 2018).…”
mentioning
confidence: 99%
“…1,3,4-Oxadiazoles are known to be associated with a broad spectrum of biological activities (Salahuddin, Elbarbary, Allam, & Hashim, 2018). 1,3,4-Oxadiazole derivatives have received considerable attention of medicinal chemists owing to their wide spectrum of useful chemical, biological, and pharmacological activities (Khan, Ahuja, & Husain, 2017).…”
mentioning
confidence: 99%